THE ROLE OF INTERCULTURAL COMMUNICATION IN SHAPING GLOBAL LITERATURE - Ne`matova Dilshoda Xurmatillo qizi; Abdurakhmanova Diana Valerevna (Ta'lim innovatsiyasi va integratsiyasi, 2024)
Abstract;  This  article  explores  Intercultural  communication  plays  a transformative role in shaping global literature by facilitating the exchange of ideas, narratives,  and  perspectives  across  cultural  boundaries.  Through  dialogue  and interaction,  writers  draw  upon  diverse  cultural  experiences  to  create  works  that transcend linguistic, geographical, and social divides. This dynamic process fosters cultural  hybridity,  allowing  global  literature  to  become  a  platform  for  mutual understanding, empathy, and innovation. Moreover, intercultural communication helps address  universal  themes,  enrich  literary  styles,  and  challenge  stereotypes,  making literature a powerful medium for global connectivity.